The role of complexity science problem-based learning with gitmind: Enhancing scientific literacy and collaboration skills of state senior high school - Sari, Intan Nurnilam; Mahanal, Susriyati; Prabaningtyas, Sitoresmi (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
The 21st-century skills needed by students today are science literacy and collaboration skills. One model that can empower science literacy and collaboration skills is the Complexity Science Problem-Based Learning (CS-PBL) model. The CS-PBL model is supported by the GitMind application, which addresses the limitations of CS-PBL by leveraging technology for collaboration. The purpose of this study was to determine the effect of the CS-PBL model assisted by GitMind on science literacy and collaboration skills of high school students in biology learning. Independent variables in this study were the CS-PBL model assisted by GitMind as an experimental group, the PBL model as a positive control, and conventional learning as a negative control. The dependent variables in this study are science literacy and collaboration skills. The research was conducted at SMAN 6 Malang, East Java, Indonesia. The population of the study was Grade XI students who were in the odd semester of the 2024/2025 school year. The sample taken from the population was grade XI students, consisting of 3 Biology specialization classes. The quasi-experimental research design used a pretest-posttest nonequivalent control group design. Students were given a pretest and a posttest in the experimental group and control group using the same instrument. Data were collected using essay tests to measure science literacy, questionnaires, and observation sheets to measure collaboration skills. Data were analyzed using a one-way ANCOVA test and followed by an LSD test before the ANCOVA test, a prerequisite test was conducted, namely a normality test and a homogeneity test. Novelty/new findings in this research are the integration of the CS-PBL model with GitMind. The results showed that the CS-PBL model assisted by GitMind was more effective in improving students' science literacy and collaboration skills than PBL and conventional learning, with the highest increase of 88.11% for science literacy and 88.53% for collaboration. Suggestions for the implementation of the CS-PBL model assisted by GitMind need to provide a more in-depth explanation of the description of the mind map task to students before learning.